Impact of Genetic Polymorphisms at the Promoter area of IL-10 Gene on Tacrolimus Level in Jordanian Renal Transplantation Recipients - Khaleel, Bara’ah; Yousef, Al-Motassem; AL-Zoubi, Mazhar; AL-Ulemat, Muhammad; Masadeh, Ahmad; Abuhaliema, Ali; AL-Batayneh, Khalid; Al-Trad, Bahaa (Journal of Medical Biochemistry, 2021)
Background Tacrolimus is a widely used immunosuppressant that prevents the solid organ transplant rejection. The pharmacokinetics of Tacrolimus show considerable variability. interleukin-10 (IL-10), in the host’s immune response after transplantation contributes to the variable CYP3A-dependent drug disposition of Tacrolimus. In current study, our aim is to evaluate the impact of single nucleotide polymorphisms (SNP) in the promoter region of of IL-10 on Tacrolimus dose requirements and the Dose Adjusted Concentration (DAC) of Tacrolimus among kidney transplantation recipients. Methods Blood levels of Tacrolimus were measured using Micorparticle Enzyme Immunoassay (MEIA) for six months post-transplantation. Genotyping analysis was utilized using specific Polymerase Chain Reaction (PCR) followed by sequencing methods for 98 Jordanian kidney transplant recipients. Results Genotyping frequencies of IL-10 (-592) were (CC/CA/AA: 38, 46.7, 15.2%); IL-10 (-819) were (CC/CT/TT: 40.4, 44.1, 15.1%); and IL-10 (-1082) were (AA/AG/GG: 42.6, 44.7, 12.8%). The impact of IL-10 (-1082) on Tacrolimus DAC was gender dependent. Men carrying at least one A allele had significantly lower DAC than men carrying GG genotyping only in the first month post-transplantation [88.2±32.1 vs. 117.5±22.5 ng/ml per mg/kg/day, p=0.04].. Conclusion Our current study showed that the interaction between gender and IL-10 -1082 affects Tacrolimus DAC in Jordanian kidney transplantation recipients during the first month post-transplantation.